2017
DOI: 10.1016/j.heliyon.2016.e00221
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Androctonus mauretanicus and Buthus occitanus scorpion venoms on electrolyte levels in rabbits

Abstract: Androctonus mauretanicus (A. mauretanicus) and Buthus occitanus (B. occitanus) scorpions, which belong to the Buthidae family, are the most venomous scorpions in Morocco. For the first time, we investigated the effects of such scorpion venoms on serum electrolytes in subcutaneously injected rabbits. For this purpose, 3 groups of 6 albinos adult male rabbits (New Zealand) were used in this experiment. Two of the groups were given a single subcutaneous injection of either crude Am venom (5 μg/kg) or Bo venom (8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Our results are in agreement with those reported previously, 22 where the LD 50 was 290 and 855 μg/kg body weight for Am and Bo , respectively, using IP injection in mice. Daoudi et al 23 reported that the Am venom had a higher lethal potency (180 μg/kg body weight) compared to Bo venom (310 μg/kg body weight). The Am venom showed an almost similar toxicity to that of the Androctonus australis hector venom (335 μg/kg body weight) via IP route.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with those reported previously, 22 where the LD 50 was 290 and 855 μg/kg body weight for Am and Bo , respectively, using IP injection in mice. Daoudi et al 23 reported that the Am venom had a higher lethal potency (180 μg/kg body weight) compared to Bo venom (310 μg/kg body weight). The Am venom showed an almost similar toxicity to that of the Androctonus australis hector venom (335 μg/kg body weight) via IP route.…”
Section: Discussionmentioning
confidence: 99%
“…Among these species, the yellow scorpion Buthus occitanus (B.occitanus) seems to be one of the most dangerous scorpions, on account of its toxic venom causing the majority of envenomation cases [9]. Although several studies had been carried out on this venom [10–13], no study has yet focused on the proteomic composition of the Moroccan B. occitanus scorpion venom despite its medical importance. Moreover, there are various strategies to screen scorpion venoms, from using conventional strategies for targeting one single toxin, to applying the most throughput equipment of screening for a detailed view of all toxic components.…”
mentioning
confidence: 99%
“…Venom's neurotoxic peptides target ion channels. Toxins alter the Na + and K + channel membrane conductance, which disrupts the neuronal in ux and results in physio pathological diseases [22].…”
Section: Discussionmentioning
confidence: 99%